Deterioro cognitivo y su repercusión en la calidad de vida de un adulto mayor de 88 años del cantón Urdaneta de la Provincia de Los Ríos - Alava Murillo, Ginger Zulay (2023)
The topic of this case study is: "Cognitive impairment and its impact on the quality of life of an adult over 88 years of age in the Urdaneta canton of the province of Los Ríos", in order to analyze how cognitive impairment affects the quality of life of an older adult, in addition to determining the main cognitive abilities affected through a psychological evaluation. The results were obtained using psychological methods and resources, including clinical history, clinical observation, clinical interviews and the use of psychological tests such as the Montreal Cognitive Assessment Test (MoCA) and the WHOQOL Quality of Life Scale - BREF. . The results obtained support the theory proposed in this case study and conclude that there is a relationship between cognitive deterioration and the quality of life of older adults. In addition, they provide guidelines to establish a therapeutic intervention scheme that addresses the present symptoms.